Integration of biosignal monitoring in sports clothing - Catarino, André P. (2012)
The present paper gives an overview of the developments achieved in biosignal and sports performance monitoring in the context of the Bioswim project. The Bioswim project aims at developing technologies for integration of conventional as well as embedding novel textile sensors for the measurement, recording and transmission of biometric and performance parameters for athlete monitoring. The study object has been a swimsuit.